A High-Quality Reference Genome for the Invasive Mosquitofish Gambusia affinis Using a Chicago Library. Issue 6 (1st June 2018) - Hoffberg, Sandra L; Troendle, Nicholas J; Glenn, Travis C; Mahmud, Ousman; Louha, Swarnali; Chalopin, Domitille; Bennetzen, Jeffrey L; Mauricio, Rodney
Abstract: The western mosquitofish, Gambusia affinis, is a freshwater poecilid fish native to the southeastern United States but with a global distribution due to widespread human introduction. Gambusia affinis has been used as a model species for a broad range of evolutionary and ecological studies. We sequenced the genome of a male G. affinis to facilitate genetic studies in diverse fields including invasion biology and comparative genetics. We generated Illumina short read data from paired-end libraries and in vitro proximity-ligation libraries. We obtained 54.9× coverage, N50 contig length of 17.6 kb, and N50 scaffold length of 6.65 Mb. Compared to two other species in the Poeciliidae family, G. affinis has slightly fewer genes that have shorter total, exon, and intron length on average. Using a set of universal single-copy orthologs in fish genomes, we found 95.5% of these genes were complete in the G. affinis assembly. The number of transposable elements in the G. affinis assembly is similar to those of closely related species. The high-quality genome sequence and annotations we report will be valuable resources for scientists to map the genetic architecture of traits of interest in this species.